2012
DOI: 10.1080/02786826.2011.637998
|View full text |Cite
|
Sign up to set email alerts
|

Condensation Particle Counter Proportionality Calibration from 1 Particle·cm−3to 104Particles·cm−3

Abstract: This article presents a process to calibrate a condensation particle counter (CPC) over the concentration range from 1 particle·cm −3 to 10 4 particles·cm −3 with traceability to SI units as realized by the National Institute of Standards and Technology (NIST). The process combines two independent steps: a proportionality assessment over the range of the CPC using a consistent diluter and an absolute calibration of the CPC with an aerosol electrometer (AE) at high concentrations. The proportionality assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Note that the comparison with an electrometer is seldom undertaken below 1,000 p/cm 3 , so information for lower concentrations regarding the linearity is lacking. However, recent studies in this area show that PNCs are linear, or at least there are ways to check their linearity for concentrations <1,000 p/cm 3 using a collection of particles on filters and TEM images (Fletcher et al 2009) or stepwise dilutions (Owen et al 2010;Sakurai and Ehara 2010). Checking the linearity of PMP PNCs with a reference PNC has shown that it is typically within 7% above 10 p/cm 3 (Giechaskiel and Bergmann 2011), and nonlinear responses >10% are rarely observed.…”
Section: Linearitymentioning
confidence: 99%
“…Note that the comparison with an electrometer is seldom undertaken below 1,000 p/cm 3 , so information for lower concentrations regarding the linearity is lacking. However, recent studies in this area show that PNCs are linear, or at least there are ways to check their linearity for concentrations <1,000 p/cm 3 using a collection of particles on filters and TEM images (Fletcher et al 2009) or stepwise dilutions (Owen et al 2010;Sakurai and Ehara 2010). Checking the linearity of PMP PNCs with a reference PNC has shown that it is typically within 7% above 10 p/cm 3 (Giechaskiel and Bergmann 2011), and nonlinear responses >10% are rarely observed.…”
Section: Linearitymentioning
confidence: 99%
“…To overcome this issue, Owen et al [6] used a fixed diluter to verify the proportionality of their CPC from 1 cm −3 to 10 4 cm −3 . Traceability to the SI was achieved by comparing the CPC to an FCAE at high concentrations, fixing the constant of proportionality.…”
Section: Introductionmentioning
confidence: 99%
“…Above this, the multiple charging limits the precision. However, there are methods to limit this issue, for instance, an additional aerodynamic size selection (Romay-Novas and Pui 1988; Hillamo and Kauppinen 1991;Owen et al 2012) or modifications of the La Mer generator (Sinclair and La Mer 1948), which produce singly charged particles (Uin et al 2009;Yli-Ojanper€ a et al 2010;Yli-Ojanper€ a et al 2012). In 2012, Yli-Ojanper€ a et al successfully applied a modified La Mer generator and a DMA for producing singly charged calibration aerosol and for conducting a FCAE-based number concentration calibration up to 1 mm.…”
Section: Introductionmentioning
confidence: 99%